2014
DOI: 10.1089/ars.2013.5206
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced miR-210 Modulates Tissue Response to Acute Peripheral Ischemia

Abstract: The physiopathological significance of miR-210 is context dependent. In the ischemic skeletal muscle it seems to be cytoprotective, regulating oxidative metabolism and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 49 publications
10
68
0
Order By: Relevance
“…Indeed, we found that miR-210 is induced in a mouse model of hindlimb ischemia (158). Accordingly, Li et al propose miR-210 as serum biomarker for atherosclerosis obliterans (78).…”
Section: Hypoxamir Peripheral Artery Disease and Wound Healingmentioning
confidence: 64%
See 1 more Smart Citation
“…Indeed, we found that miR-210 is induced in a mouse model of hindlimb ischemia (158). Accordingly, Li et al propose miR-210 as serum biomarker for atherosclerosis obliterans (78).…”
Section: Hypoxamir Peripheral Artery Disease and Wound Healingmentioning
confidence: 64%
“…However, miR-210-HIF1A positive feedback may not be present in all tissues and/or physiopathological conditions. Indeed, we found that miR-210 blockade did not affect HIF1A-pathway activation in a mouse model of acute hindlimb ischemia (158).…”
Section: Hypoxia-inducible Factor 1: An Mirna-mediated Modulatormentioning
confidence: 77%
“…Ischemic brain injury, known as ischemic stroke, is caused by occlusion of a blood vessel, and the remarkable decrease in regional cerebral blood flow leads to hypoxia, glucose loss and brain damage [29]. Recent experiments demonstrated that ischemia-induced miRs act as negative regulators of genes, taking part in the treatment for acute and chronic ischemia [30, 31]. In this study, we investigated the effect of miR-381 targeting LRRC4 by the SDF-1/CXCR4 signaling pathway on the repair of nerve injury in rats with acute cerebral ischemia after CLB.…”
Section: Discussionmentioning
confidence: 99%
“…The most notable hypoxia-miR, miR-210, is induced in ECs in a HIF-1α dependent manner [100]. Notably, miR-210 is upregulated also in cardiomyocytes undergoing hypoxia [101] and in whole ischemic muscles [102]. Induction of miR-210 in ECs is instrumental in downregulating genes that impair tubulogenesis and VEGF-induced chemotaxis, like EphrinA3 (EFNA3) [100] and apoptosis [101].…”
Section: Ischemic Injury and Micrornasmentioning
confidence: 99%
“…Delivery of miR-210 LNA in a model of hind-limb ischemia increases cell apoptosis and necrosis, further decreases capillary density and impairs limb perfusion. Gene expression analysis of ischemic gastrocnemius shows that the most affected pathways following by miR-210 inhibition were redox balance in cells and mitochondria function [102]. …”
Section: Ischemic Injury and Micrornasmentioning
confidence: 99%